Quality Improvement Model of Nursing Education in Muhammadiyah Universities Toward Competitive Advantage - Abdul Aziz Alimul Hidayat; Musrifatul Uliyah; Sukadiono Sukadiono (Jurnal Ners, 2017)
Introduction: Most of (90,6%) nursing education quality in East Java was still low (BAN-PT, 2012). It was because the quality improvement process in nursing education generally was conducted partially (random performance improvement). The solution which might be done was through identifying proper quality improvement model in Nursing Education toward competitive advantage.Method: This research used survey to gain the data. The research sample was 16 Muhammadiyah Universities chosen using simple random sampling. The data were collected with questionnaires of 174 questions and documentation study. Data analysis used was Partial Least Square (PLS) analysis technique.Result: Nursing education department profile in Muhammadiyah Universities in Indonesia showed of 10 years establishment, accredited B and the competition level in one city/regency was averagely more than three Universities becoming the competitors. Based on the quality improvement model analysis of nursing education toward competitive advantage on Muhammadiyah Universities, it was directly affected by the focus of learning and operasional process through human resources management improvement, on the other hand information system also directly affected on quality improvement, also affected quality process components; leadership, human resources, focus of learning and operational process. In improving human resources would be directly influenced with proper strategic planning. Strategic planning was directly influenced with leadership. Thus, in improving quality of nursing education, the leadership role of department, proper information system, and thehuman resources management improvement must be implemented.Conclusion: Quality improvement model in nursing education was directly determined with learning and operational process through human resources management along with information system, strategic planning factors, and leadership. The research finding could be developed in quality analysis application program.